Sustainable supply of critical materials for water electrolysers and fuel cells - Dengye Xun; Ming Liu; Han Hao; Xin Sun; Yong Geng; Fengqi You; Hao Dou; Haoyang Li; Zhenyu Dong (Communications Earth & Environment)
Abstract Water electrolysers and fuel cells are key technologies for global energy transition. Many materials used in them are critical, facing supply challenges. We compile challenges and opportunities for the sustainable supply of these critical materials. Three types of electrolysers (alkaline, polymer electrolyte membrane, and solid oxide) and two types of fuel cells (polymer electrolyte membrane and solid oxide), along with eight associated critical materials (nickel, zirconium, platinum, iridium, titanium, lanthanum, yttrium, and strontium) are considered. Material supply sustainability is reviewed from six dimensions: supply disruption risk, environmental impact, social impact, resource depletion pressure, circularity, and substitutability. We show that the devices perform differently in the six dimensions. Major challenges for the alkaline electrolyser are resource depletion pressure and substitutability, while the challenge for polymer electrolyte membrane electrolysers is the supply disruption risk. Regarding solid oxide electrolysers, challenges are identified in supply disruption risk, resource depletion pressure, and circularity dimensions.